Dissemination of The Fit and Proper Test Regarding The Appointment of The Board of Directors of The Tangerang Regency Regional Company (PERUMDAM) - Mas Iman Kusnandar; Refi Pratiwi; Muhammad Abduh (MOVE: Journal of Community Service and Engagement, 2021)
This socialization activity aims to introduce the Fit and Proper Test to participants of the prospective Board of Directors of Perumdam Tangerang Regency before the Feasibility and Fit Test is held. Feasibility Test and Proper Test to maintain the independence of the company. The method of implementing activities in the acceptance of prospective candidates for the Board of Directors consists of several stages, namely starting from administrative selection, selection of fit and proper test, interview test. This socialization activity must be carried out every time a Feasibility and Fit Test will be carried out because there is still a risk regarding a lack of understanding of the technicalities of the Fit and Proper Test. With the fit and proper test, it produces leaders who are intellectually competent as well as cognitive and emotional.